â€œINCREASING TAX COMPLIANCE THROUGH TRUST AND POWERâ€: EMPIRICAL STUDY OF SLIPPERY SLOPE FRAMEWORK IN ASEAN - Brata, Farid Wisnu; Riandoko, Riko (Scientax, 2020)
This paper contributes to the empirical literature regarding the assumptions of the Slippery Slope Framework using cross-country data in the regional economy. Some studies in this area have tested the assumptions of the framework using primary data collected through surveys with real taxpayers or students as subjects, and some studies have tested the framework using statistical data generated from an institutional database. This study tested these assumptions using statistical data generated from the institutional database i.e., Asian Development Bank and World Bank. Align with prior studies that confirm the effect of trust and power on tax compliance, this study hypothesizes that tax compliance can be explained by the existence of both trust and power. It further hypothesizes that tax compliance can be explained by the interaction between trust and power as well. This study is based on 10 ASEAN countries as the population, consisting Indonesia, Thailand, Malaysia, Singapore, Philippine, Brunei, Vietnam, Laos, Myanmar, and Cambodia. The empirical result from our sample represents that trust and power interact in explaining tax compliance.